PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN PANCASILA SD NEGERI 064034 MEDAN - Angela Mericci Alpa Manurung; Irmnina Pinem; Eka Margareta Sinaga; Ester Julinda Simarmata; Paskah Sri Ulina Tarigan; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by Wordwall media on student learning motivation in Pancasila Education subjects. The research method used is quantitative method with experimental design. The research subjects were fourth grade students of SD Negeri 064034 Medan, totaling 23 people. Data collection techniques are done through questionnaires that have been tested for validity and reliability. The pretest results showed an average value of 44.91 in the category of needing guidance, while the posttest results increased to 77.74 in the developing category. The Pearson correlation test shows a coefficient value of 0.626 which is included in the strong category, with a significance of 0.001, meaning that there is a strong positive relationship between the problem-based learning model assisted by wordwall media on student learning motivation. Furthermore, the results of hypothesis testing using the t-test obtained the value of tcount  ttable  , which is 3,683  1,714, which means that there is a significant influence between the use of problem-based learning models assisted by wordwall media on student learning motivation.